Destruction to Mangrove Forests in East Luwuk, Banggai Regency, Central Sulawesi - Ris Hadi Purwanto; Lies Rahayu Wijayanti Faida; Sumardi; Kalsum, Ummu (Talenta Publisher, 2022)
According to the results of interactions between humans and mangrove forests, the causes of mangrove forest destruction are developing very dynamically. In the sub-district of East Luwuk, Banggai Regency, this study aims to determine the causes of mangrove forest damage. With descriptive analysis, this study utilizes qualitative methods. To determine the factors causing damage to mangroves was done by purposive sampling through interviews. The results showed that the damage to mangrove forests was caused by the conversion of mangrove forests into ponds, rice fields, and settlements. By carrying out restoration, rehabilitation, and restoration of damaged areas and recommending pond management by implementing a silvofishery pattern that can meet community welfare and maintain the survival of the mangrove ecosystem.